Gender Power Relations on Sexual and Reproductive Health Services among Youth in Southwest Nigeria - Oluwadare, Christopher Taiwo; Akerele, Oluwatumininu; Akerele, Nelson; Igbekoyi, Kayode Emmanuel (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Reproductive health implies that people are able to have a satisfying and safe sex life and that they have the capability to reproduce and the freedom to decide if, when and how often to do so. This study investigated gender power dynamics and sexual and reproductive health (SRH) services among youth in Southwest Nigeria, using Connell's Theory of Gender and Power to explain the study. The study employed descriptive research design, in which multistage sampling techniques was adopted and questionnaire was used to gather information from 1200 respondents made up of youths aged 15 and 35 in Ekiti, Osun, and Ondo. Results: The findings from the study revealed a concerning lack of understanding of SRH services among youth, with knowledge often rooted in social myths and misconceptions. For example, 59% believed people with HIV always appear unhealthy. While most understood major SRH components like contraception and sexual violence, only 29% of males were familiar with periodic abstinence, preferring condoms. The study found low SRH service uptake among males, attributed to service-related barriers. Interestingly, while 78% agreed that either party can initiate condom use, 34% of males perceived a girl's suggestion as distrustful. Urgent policy reforms are recommended including establishing youth-friendly SRH centers, educational campaigns, and promoting equitable decision-making to empower youth and improve SRH service access. A gender disparity emerged, with females showing higher awareness of various contraceptive methods, potentially reinforcing traditional gender roles. This aligns with previous findings indicating greater HIV awareness compared to other SRH aspects. Societal norms dictate gender-specific risk-taking behaviors, particularly among males, impacting women's health. These behaviors include avoiding condoms, substance abuse, and reluctance to seek HIV testing and treatment. This can lead to issues like violence, STIs, and unintended pregnancies. Based on the findings, the study concluded that the gender disparity in the utilization of reproductive health services with females reporting higher usage compared to males. The study therefore recommends that there should be comprehensive and targeted educational programs that specifically address gaps in knowledge concerning sexual and reproductive health. Keywords: Gender, Gender Power Relation, Youth Sexual and Reproductive Health, Contraceptive Use